The derivation of verbs in Old English and Middle English - Castillo, Concha (Complutense Journal of English Studies, 2022)
Within the framework of minimalist syntax, it is argued that the core-syntax derivation of verbs in OE and ME (up to approx. 1450) is regulated by two licensing T(ense) heads (that is, two T Probes) plus a licensing v head (or v Probe), all of which are in charge of interpreting τ–features. v acts as Probe of v-0 (its Goal) in order to interpret [+/–past] τ–features for strong verbs. This capacity of v is argued to rely on the ablaut distinction between Pret. 1 and Pret. 2, since ablaut is determined by the specific [person] of the subject and must therefore be syntactically derived. This situation comes to an end in the period ca. 1450. Of the two T Probes, [T T] is in charge of interpreting [past] τ–features for weak verbs, and it expones as a /d/ suffix. The other T Probe is labelled here [TAgrT] and is in charge of interpreting [+/–past] τ–features with an additional φ–interpretation. A proof for the existence of this Probe is for the agreement (person and number) endings to co-vary with Present tense and Past tense, despite cases of syncretism between exponents or Vocabulary Items. [TAgrT] is the Probe that is obligatorily present in the licensing of any kind of verb in OE (and also in ME) –whether weak or strong– and therefore it must be held responsible for the configurational status of the latter as a T language.
Keywords: t-features; t-interpretation; phi-interpretation; weak verbs and strong verbs in OE and in ME; T Probes; v Probe